Theory and practice of natural computing : Fourth International Conference, TPNC 2015, Mieres, Spain, December 15-16, 2015, proceedings /: Fourth International Conference, TPNC 2015, Mieres, Spain, December 15-16, 2015, proceedings. (2015) - Unknown
No abstract available